On the identities of the sesarmid crabs, Sesarma villosum A. Milne-Edwards, 1869, and Clistocoeloma suvaense Edmondson, 1951, with the description of a new species from the West Pacific (Decapoda, Brachyura, Thoracotremata) - Lee, Bee Yan; Ng, Ngan Kee; Ng, Peter K. L. (Zootaxa, 2023)
The identities of two sesarmid crabs, Clistocoeloma villosum (A. Milne-Edwards, 1869), and C. suvaense Edmondson, 1951, both currently in Clistocoeloma A. Milne-Edwards, 1873, are poorly known and the types have not been studied in detail since their description. Clistocoeloma villosum, supposedly widespread, has been recorded from Madagascar and East Africa to Singapore, Japan, Korea, and Samoa. Clistocoeloma suvaense is only known for certain from one male collected from its type locality, Fiji. The taxonomy of C. villosum, and C. suvaense is clarified on the basis of the type specimens from Samoa and Fiji, respectively. A new species, which has long been confused with C. villosum, is described from Southeast Asia and Western Pacific.